Mesenchymal Stem Cell-derived Exosomes Improve Functional Recovery in Rats After Traumatic Brain Injury with a Broad Therapeutic Window. (16th November 2020) - Mahmood, Asim; Zhang, Yanlu; Zhang, Yi; Zhang, Zhenggang; Chopp, Michael; Xiong, Ye
Abstract: INTRODUCTION: Mesenchymal stem cell (MSC)-derived exosomes are emerging as an important therapy in regenerative medicine with broad applications. METHODS: Male rats were injured with controlled cortical impact. In the dose response study a single intravenous injection of exosomes (50, 100, 200 μg/rat) or vehicle (n = 8/group) was administered 1 day after TBI. In the therapeutic window study, an intravenous injection of 100 μg exosomes or vehicle was administered on days 1, 4, or 7 after injury (n = 8/group). Neurological function was assessed using Neurological Severity Scores (NSSs), Footfault and Morris Water Maze (MWM) tests. Animals were sacrificed 35 days after TBI and tissues were analyzed using immunohistological studies. RESULTS: Compared to the vehicle, regardless of the dose and delay in treatment, exosome treatment significantly improved sensorimotor and cognitive function (NSS, MWM & Footfault tests), reduced hippocampal cell loss, promoted angiogenesis and neurogenesis, and reduced neuroinflammation. Maximum therapeutic benefit was seen with 100 μg dose. The time-dependent treatment data demonstrated that although 1-day post TBI treatment provided greatest improvement, significant functional and histological benefit was also seen with the other two delayed treatments (4 & 7 days post TBI). CONCLUSION: These results indicate that exosomes have a wide range of effective doses for treatment of TBI with a therapeutic window of at least 7 days post injury. This efficacy of delayed treatment enhances the promise of exosome treatment as a potential therapeutic intervention for TBI.